Oncological outcome of patients treated surgically with oncoplastic breast surgery: a single centre analysis - Iswary, Fermin; Das, Bhabesh Kumar; Paul, Rajiv; Kalita, Dwipen (International Surgery Journal, 2022)
Background: Oncoplastic breast surgery is a well-established approach that aims to maintain the quality of life by using plastic surgery techniques without compromising the oncological outcome. This study aimed to demonstrate the effective oncoplastic surgical practice with low rates of perioperative complication and high patient reported outcome. Methods: A prospective observational and systematic review comprised of 50 patients with T1- T3 and T4B lesions treated with Level I and Level II oncoplastic breast surgery techniques in a single centre. Patient demography, procedure and outcome data were collected. The patient satisfaction and quality of life were assessed using Breast Q Module questionnaire. Results: The greatest number of cases were seen in the age group 30-40 years with T2 lesions with next T4B lesions in the same age group. Three patients (6%) experienced complication requiring intervention, and all patients had margins free of tumour. Patient satisfaction scores were higher in the postoperative period. Conclusions: Our study even though has a smaller number of patients and less duration of study period showed a good result with regards to the patient reported outcomes.